Using Simple, Decision-Centered, Scenario-Based Planning to Improve Local Coastal Management. Issue 4 (2nd October 2019) - Norton, Richard K.; Buckman, Stephen; Meadows, Guy A.; Rable, Zachary
Abstract: Problem, research strategy, and findings: Scenario-based planning offers the promise of enhancing local coastal management given uncertainties from shoreline dynamics and climate change. Deploying it can require substantial capacity, however, or can obscure the key policy choices a community faces. We set out to develop and test a simple, decision-centered approach to scenario-based planning as a way to improve local management of coastal shorelands through master plans, focusing on coastal hazard mitigation. We also looked for ways to use basic spatial analysis techniques and off-the-shelf data sources that could be manipulated to generate meaningful and reasonably accurate analyses. We find the simplified and decision-centered methods we have developed can provide useful information for local decision makers. We also find the quality of the master plans adopted by two partner localities that used our scenario-based planning methods substantially exceeds the quality of comparison plans with regard to coastal management. Takeaway for practice: Using simplified, decision-centered, scenario-based planning methods can facilitate enhanced hazard mitigation analysis and policy adoption in local master plans. Those methods necessarily will and should be tailored to the unique political and physical conditions of the community, as demonstrated by the leadership provided in the localities studied here.